2012
DOI: 10.1002/jbm.a.34356
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced osteogenesis by collagen‐binding peptide from bone sialoprotein in vitro and in vivo

Abstract: Bone sialoprotein (BSP) is a mineralized, tissue-specific, and noncollagenous protein. The binding of BSP to collagen is thought to be important for the initiation of bone mineralization and formation. In this study, we elucidated the osteogenic efficiency of the collagen-binding (CB) peptide derived from BSP in vitro and in vivo. The CB peptide increased osteoblastic differentiation marker gene and protein expression without affecting cell proliferation. The osteoblastic differentiation by the CB peptide is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Epidemiological studies reported that milk is a well-known bone health-promoting agent [12,13]. As the osteoblast proliferation is crucial, part of the bone formation or remodeling osteoblast proliferation effect is used for screening osteogenic bioactive peptides [28,31,[33][34][35].…”
Section: Identification Of Osteogenic Peptides In 1-kda Fraction Of Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies reported that milk is a well-known bone health-promoting agent [12,13]. As the osteoblast proliferation is crucial, part of the bone formation or remodeling osteoblast proliferation effect is used for screening osteogenic bioactive peptides [28,31,[33][34][35].…”
Section: Identification Of Osteogenic Peptides In 1-kda Fraction Of Pmentioning
confidence: 99%
“…1). MTT is a simple reliable method to evaluate osteoblast proliferation [27][28][29][30][31]; hence, the proliferation effect of PT hydrolysates and peptides was evaluated by MTT method. At lower concentration, PT hydrolysates did not show any proliferation effect, but it started inducing proliferation of calvarial cells at 50 µg/ ml, and the proliferation effect remained constant up to 100 µg/ml.…”
Section: Effect Of Pepsin-trypsin Hydrolysates On Proliferation Of Osmentioning
confidence: 99%
“…antiresorptive or osteogenic), is one of the central strategies being explored for bone repair [3,4,11]. However, promotion of bone regeneration through inflammatory signals remains largely unexplored, in spite of evidence that inflammation may have a positive role in bone remodeling.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, the role of immune cells and inflammatory mediators in biomaterial-mediated bone repair/regeneration has been considerably overlooked. It is not uncommon to find studies reporting the absence of (or mild) inflammatory reactions, associated with degradable biomaterials developed for tissue repair/regeneration [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The differentiation of multipotent MSCs into osteogenic cells depends on the spatially coordinated activities of multiple signalling pathways that include growth factors (GFs) and extracellular matrix (ECM) components [7][8][9]. Considerable attention has been devoted to extrinsic factors that orchestrate determination and differentiation of MSCs [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%